2011
DOI: 10.1021/bi2005762
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Molybdenum Center of Mitochondrial Amidoxime Reducing Component (mARC) by Pulsed EPR Spectroscopy and 17O-Labeling

Abstract: Mitochondrial amidoxime reducing components (mARC-1 and mARC-2) represent a novel group of Mo containing enzymes in eukaryotes. These proteins form the catalytic part of a three-component enzyme complex known to be responsible for the reductive activation of several N-hydroxylated prodrugs. No X-ray crystal structures are available for these enzymes as yet. Previous biochemical investigation by B. Wahl et al. (J. Biol. Chem. 285 (2010) 37847–37859) has revealed that two of the Mo coordination positions are occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…7) that an extra sulfur atom might be required as additional Mo-ligand in Moco in YcbX or YiiM, as found in the Xanthine Oxidase family (Schwarz et al 2009;Iobbi-Nivol and Leimk€ uhler 2012;Hille 2013), was also considered, as the precise nature of Moco in YcbX and YiiM is presently undetermined. Recent evidence indicating that the corresponding eukaryotic proteins, human mARC or green algal crARC, do not carry an additional Mo=S ligand on their Moco Chamizo-Ampudia et al 2011;Rajapakshe et al 2011). Also, our results show that iscS and tusA mutants are chlorate resistant (see Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…7) that an extra sulfur atom might be required as additional Mo-ligand in Moco in YcbX or YiiM, as found in the Xanthine Oxidase family (Schwarz et al 2009;Iobbi-Nivol and Leimk€ uhler 2012;Hille 2013), was also considered, as the precise nature of Moco in YcbX and YiiM is presently undetermined. Recent evidence indicating that the corresponding eukaryotic proteins, human mARC or green algal crARC, do not carry an additional Mo=S ligand on their Moco Chamizo-Ampudia et al 2011;Rajapakshe et al 2011). Also, our results show that iscS and tusA mutants are chlorate resistant (see Fig.…”
Section: Discussionsupporting
confidence: 71%
“…; Rajapakshe et al. ). Also, our results show that iscS and tusA mutants are chlorate resistant (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been demonstrated that mARC-2 has a solvent-exchangeable equatorial oxygen ligand, most likely a Mo=O. 360 mARC proteins represent the simplest vertebrate molybdenum enzymes in that they are monomeric proteins consisting of solely a MOSC domain and bind only one prosthetic group, the molybdenum cofactor. It should be borne in mind, however, that these enzymes do not function as stand-alone proteins but rather act in concert with other redox-active components.…”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…2 H, 17 O, 33 S labeling have been used together with pulse EPR investigation, which confirms sevencoordination or six-coordination of the Mo center. 67…”
Section: Epr Spectroscopymentioning
confidence: 99%